The role of emotional regulation in predicting psychological well-being among physical education teachers - Purnomo, Reza Asep Adi; Jannah, Miftakhul (UIR Press, 2025)
Background: Physical education teachers play an important role in instilling an active lifestyle and social values. In relation to this important role, teachers need to have good emotional regulation and psychological well-being to support their teaching. There is a need for research that examines the involvement of emotional regulation in shaping the psychological well-being of physical education teachers. Research Objectives: The purpose of this research is to predict the role of emotion regulation on the psychological well-being of physical education teachers. Methods: Quantitative research was chosen as the research method with data processed using simple regression analysis. Research data were obtained from physical education teachers who are undergoing pre-service teacher training at a higher education institution. The questionnaire obtained data from 74 respondents and was processed on SPSS 26.0.0. Finding and Results: Based on the findings, it was discovered that emotional regulation negatively predicts psychological well-being. The meaning of these results is that the higher the emotional regulation, the lower the psychological well-being of physical education teachers. Conclusion: It is concluded that the negative coefficient of emotion regulation is able to predict the psychological well-being of physical education teachers. These findings differ from several previous studies. The results of this study, on the other hand, are also able to contribute to relevant parties by providing emotion regulation training strategies to enhance psychological well-being. In addition, the new findings recommend to other researchers to explore what types of emotion regulation strategies may lead to a decline in psychological well-being.